2017
DOI: 10.1186/s12943-017-0640-9
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90β promoted endothelial cell-dependent tumor angiogenesis in hepatocellular carcinoma

Abstract: BackgroundVascular endothelial growth factor receptors (VEGFRs) are the major receptors involved in endothelial cell-dependent tumor angiogenesis. There are studies account for the effects of Hsp90 on angiogenesis, but the role and mechanism of Hsp90β isoforms and NVP-BEP800, a specific inhibitor of Hsp90β, in tumor angiogenesis is rarely mentioned.MethodsImmunohistochemistry and statistical analysis was used to evaluate the correlation between Hsp90β expression, CD31 endothelial cell-dependent vessel density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…The secondary antibody was subsequently added using an horseradish peroxidase-polymer anti-mouse/ rabbit IHC kit (Maixin Biotech) for 1 hour at room temperature. Then, the samples were developed with diaminobenzidine reagent, counterstained with hematoxylin and mounted with permount (33). The immunohistochemistry score was calculated by multiplying the intensity (0 ¼ negative, 1 ¼ canary yellow, 2 ¼ claybank, 3 ¼ brown) and the positive cell percentage scores (1 ¼ less than 25%, 2 ¼ 25% to 50%, 3 ¼ 51% to 75%, 4 ¼ more than 75%).…”
Section: Ihc Assay and Analysismentioning
confidence: 99%
“…The secondary antibody was subsequently added using an horseradish peroxidase-polymer anti-mouse/ rabbit IHC kit (Maixin Biotech) for 1 hour at room temperature. Then, the samples were developed with diaminobenzidine reagent, counterstained with hematoxylin and mounted with permount (33). The immunohistochemistry score was calculated by multiplying the intensity (0 ¼ negative, 1 ¼ canary yellow, 2 ¼ claybank, 3 ¼ brown) and the positive cell percentage scores (1 ¼ less than 25%, 2 ¼ 25% to 50%, 3 ¼ 51% to 75%, 4 ¼ more than 75%).…”
Section: Ihc Assay and Analysismentioning
confidence: 99%
“…Furthermore, HSP90 interacts with and inhibits the degradation of 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCR), the rate-limiting enzyme of mevalonate pathway that is essential for cancer progression [74]. Since HSP90 serves to promote the transcription and expression of vascular endothelial growth factor receptors (VEGFRs), the major receptors involved in endothelial cell-dependent tumor angiogenesis, HSP90 overexpression leads to the enhanced proliferation, migration, invasion, and tube cell-dependent tumor angiogenesis in vitro and in vivo [75]. In breast cancer, increased levels of HSP90 are often detected, and HSP90 functions to stabilize the heightened activation of estrogen receptor (ErbB)-dependent PI3K/AKT and ERK signaling pathways.…”
Section: Role Of Hsp90 In Cancer Developmentmentioning
confidence: 99%
“…Hsp90β plays an important role in the growth and proliferation of tumors [26]. Recent study have revealed that Hsp90β promoted endothelial cell-dependent tumor angiogenesis in hepatocellular carcinoma [27]. Moreover, studies have shown that Hsp90β is highly expressed in glioma tissue, and its inhibitors can inhibit the migration and invasion of glioma cells and inhibit the secretion of vascular endothelial growth factor [28].…”
Section: Introductionmentioning
confidence: 99%